Impact of Interactive Education and Hands-On Training on Nurses' Chronic Wound Care Knowledge - Mardiana Mochamad Ramdan; Fitri Nurlina; Bayu Brahmantia (Journal of health research and technology, 2026)
Introduction: Chronic wound management remains a major challenge in nursing because of its complexity, prolonged healing process, and impact on patient outcomes. Despite the importance of evidence-based wound care, nurses' knowledge of modern wound management remains inadequate, underscoring the need for effective educational interventions. This study examined the effect of interactive education and hands-on modern wound care training on nurses' knowledge of chronic wound prevention and management. Methods: A quantitative study employing a pre-experimental one-group pretest-posttest design was conducted among 33 nurses recruited through random sampling. Data were collected using a modern wound care knowledge questionnaire administered before and after the intervention. The intervention consisted of interactive educational sessions and supervised hands-on training in modern wound care practices. Descriptive statistics were used to summarize the data, while the Wilcoxon Signed Rank Test was performed to evaluate differences in knowledge scores before and after the intervention. Results: The median knowledge score increased from 80 before the intervention to 88 after the intervention. The mean knowledge score improved from 77.82 ± 15.37 to 84.00 ± 8.60. Statistical analysis revealed a significant difference between pretest and posttest scores (Z = −2.540, p = 0.011). The effect size (r = 0.44) indicated a moderate educational effect. Conclusion: Interactive education combined with hands-on training significantly improved nurses' knowledge of chronic wound prevention and management. Integrating active and experiential learning into continuing professional development may strengthen nursing competence and support evidence-based wound care.